(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
After defeating the army of John I of Castile at the Battle of Aljubarrota, the King vowed to have a monastery built near the battlefield as a token of his gratitude to the Virgin Mary, to commemorate the events of that day, the 14th of August, 1385. Following the example of his royal predecessors, who over time favored or founded monastic institutions to serve as their final resting places both for themselves and their closest relatives the Monastery of Saint Mary of Victory (Mosteiro de Santa Maria da Vitria) would become the symbolic seat of his House, the newly established Avis dynasty, which was just taking its first steps. Having been proclaimed king only a few months earlier, in Coimbra, at the Cortes that gathered between late March and April 6 of that same year, King John I was the natural son of King Pedro I, and thus half-brother to King Ferdinand I, who had passed away on October 22, 1383.**